(3GdJfhjQ TQM GdLGeY GdUZjQs - (3eMeO Hf ESeGYjd Hf UdGM Hf eMeO GdMSfj, GdcMdGfj Ke GdUfYGfj, CHh EHQGgje, YR GdOjf, GdeYQha cCSdGag HGdCejQ, J (B1182 (3g` s
(3ChdgG (B:s
(3aEf Gddg hdg GdMeO hGdKfGA bOef HGdaQGZ ef GdLRA GdChd gPG hGf GdTQhY ai GdLRA GdKGfi bO SbfG ajg eG jSQg Gddg ef Md CdaGXg hEHGfg GdeYGfi s
(3BNQgG (B:s
(3dYdg ef GdQGhi Ch Gfg efg UdYe , hbO LGA ai ZjQg ef eSjQI NeSeGFI YGe s
(3CJe GdeDda GdJCdja SfI (B1154(3g`s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHgG HYfGjI GdeDda (B_ (3CHfg ceG hQO ai BNQ GdLRA GdQGHY ef GdfSNI faSgG s
(3cJH GdeJf HGdMeQI s
(3ChQGbgG GdCNjQg Hbde eNJda s
Keywords: (3GdMOjK h GdeUWdMs